Counselors' Attitudes Towards Working With Clients With Substance Use Disorders. (July 2020) - Cornfield, Zachary A. D.; Hubley, Anita M.
Substance use disorders (SUDs) are a significant and growing problem in all walks of life in Canada and the United States. Counselors are increasingly likely to have clients with SUDs regardless of their area of expertise. There is limited research on counselors' attitudes towards working with such clients, or the factors that contribute to these attitudes. In an online survey of 263 Canadian counselors, we found attitudes were mostly positive, although statistically significantly less positive than toward working with clients with major depression. Numerous variables showed significant bivariate relationships with attitudes towards working with clients with SUDs, but only more frequent contact with such clients, fewer workplace situational constraints, and less frequent feelings of anger towards such clients remained as significant predictors of more positive attitudes in a regression analysis. Our research highlights the importance of providing more support for counselors to ensure better service to clients with SUDs.